1990
DOI: 10.1029/jb095ib06p08859
|View full text |Cite
|
Sign up to set email alerts
|

Heat flow, tectonics, and fluid circulation at the toe of the Barbados Ridge Accretionary Prism

Abstract: Detailed patrems of near surface tectonics and heat flow were investigated at two locations at the toe of the Barbados Ridge accretionary prism. At the two locations, in the thickly sedimented southern portion of the prism near 12ø202q and in the northern area drilled during Ocean Drilling Program (ODP) leg 110 near 15ø322q, relative highs of heat flow were associated with zones of thrusting. We attribute them to upward advection of water rising from the d6collement along faults through the sediments. In the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 17 publications
2
46
0
1
Order By: Relevance
“…5) This value is fairly coherent with surface heat-flow determinations in the area (Foucher et al, 1990).…”
Section: Sediment Thermal Conductivity and Heat Flowsupporting
confidence: 73%
See 1 more Smart Citation
“…5) This value is fairly coherent with surface heat-flow determinations in the area (Foucher et al, 1990).…”
Section: Sediment Thermal Conductivity and Heat Flowsupporting
confidence: 73%
“…Also, the constant heat flow across the décollement implies that the horizontal flow rates along it do not exceed values of the order of 10 m 3 /yr per meter along strike of the subduction zone. This estimate is at least ten times smaller than initially proposed by Fisher and Hounslow (1990) and Foucher et al (1990).…”
Section: Discussionmentioning
confidence: 47%
“…The lateral and vertical pressure gradients that are established cause fluids to be expelled locally or diffusely from the thickening section (Moore et al, 1988;Davis et al, 1990;. The rates and total volumes of fluid flow are not as great as those in axial hydrothermal systems, although thermal and particularly chemical fluxes can be locally significant (Gieskes et al, 1990;Davis et al, 1990;Langseth et al, 1990;Foucher et al, 1990), and the integrated effect of the flux of expelled fluids on the diagenesis and alteration of the sediment section is suspected to be large (Kulm and Suess, 1990;Hyndman and Davis, in press).…”
Section: Holes In Accretionary Prismsmentioning
confidence: 99%
“…Numerous studies have indicated that the décollement, intraprism faults, highly permeable (sandy) layers, and mud volcanoes provide conduits for water flow to escape. Detailed studies of the Barbados (Foucher et al, 1990;Fisher and Hounslow, 1990), Oregon-Washington , and Japan (Henry et al, 1989) accretionary wedges document that rates of fluid expulsion from vents and mud volcanoes can be as great as, or significantly greater than, the total rate of fluids entering the subduction zone, implying that fluid vents and mud volcanoes are transient features. The Costa Rica margin probably has few sandy layers, so any elevated permeability is most likely fracture permeability.…”
Section: Fluid Effectsmentioning
confidence: 99%